Rs Aggrawal 2019 2020 Solutions for Class 6 Math Chapter 6 Simplification are provided here with simple step-by-step explanations. These solutions for Simplification are extremely popular among Class 6 students for Math Simplification Solutions come handy for quickly completing your homework and preparing for exams. All questions and answers from the Rs Aggrawal 2019 2020 Book of Class 6 Math Chapter 6 are provided here for you for free. You will also love the ad-free experience on Meritnation’s Rs Aggrawal 2019 2020 Solutions. All Rs Aggrawal 2019 2020 Solutions for class Class 6 Math are prepared by experts and are 100% accurate.

#### Question 1:

Simplify:

Given expression:
= 21 - 12 $÷$ 3 ⨯ 2
= 21 - 4 ​⨯ 2               [Performing division]
= 21 - 8                     [Performing multiplication]
= 13                          [Performing subtraction]

#### Question 2:

Simplify:

Given expression:
= 16 + 8 $÷$ 4 - 2 ⨯ 3
= 16 + 2 - 2 ​⨯ 3               [Performing division]
= 16 + 2 - 6                     [Performing multiplication]
= 18 - 6                           [Performing addition]
= 12                               ​ [Performing subtraction]

#### Question 3:

Simplify:

Given expression:
= 13 - (12 - 6 ÷ 3 )
= 13 - (12 - 2)       [Performing division]
= 13 - 10 = 3
[Performing subtraction]

#### Question 4:

Simplify:

Given expression:
= 19 - [4 + {16 - (12 - 2)}]
19 - [4 + {16 - 10}]                        [Removing parentheses]
= 19 - [4 + 6]                                    [Removing braces]
= 19 - 10                                           [Removing square brackets]
= 9

#### Question 5:

Simplify:

Given expression:
= 36 - [18 - {14 - (15 - 4 ÷ 2 × 2)}]
36 - [18 - {14 - (15 - 2 × 2)}]                   [Performing division]
36 - [18 - {14 - (15 - 4)}]                         [Performing multiplication]
=
36 - [18 - {14 - 11}]                                [Removing parentheses]
=
36 - [18 - 3]                                            [Removing braces]
​= 36 - 15                                                   [Removing square brackets]
= 21

#### Question 6:

Simplify:

Given expression:
= 27 - [18 - {16 - (5 - $\overline{)4-1}$)}]
=
27 - [18 - {16 - (5 - 3)}]                       [Removing bar]
=
27 - [18 - {16 - 2}]                              [Removing parentheses]
27 - [18 - 14]                                       [Removing braces]
= 2
7 - 4                                                 [Removing square brackets]
​= 23

#### Question 7:

Simplify:

Given expression:

#### Question 8:

Simplify:

Given expression:

#### Question 9:

Simplify:

The given expression

#### Question 10:

Simplify:
$5\frac{1}{7}-\left\{3\frac{3}{10}÷\left(2\frac{4}{5}-\frac{7}{10}\right)\right\}$

Given expression:

#### Question 11:

Simplify:
$9\frac{3}{4}÷\left[2\frac{1}{6}+\left\{4\frac{1}{3}-\left(1\frac{1}{2}+1\frac{3}{4}\right)\right\}\right]$

Given expression:

#### Question 12:

Simplify:
$4\frac{1}{10}-\left[2\frac{1}{2}-\left\{\frac{5}{6}-\left(\frac{2}{5}+\frac{3}{10}-\frac{4}{15}\right)\right\}\right]$

Given expression:

#### Question 13:

Simplify:

Given expression:

#### Question 14:

Simplify:
$4\frac{4}{5}÷\left\{2\frac{1}{5}-\frac{1}{2}\left(1\frac{1}{4}-\overline{\frac{1}{4}-\frac{1}{5}}\right)\right\}$

Given expression:

#### Question 15:

Simplify:
$7\frac{1}{2}-\left[2\frac{1}{4}÷\left\{1\frac{1}{4}-\frac{1}{2}\left(\frac{3}{2}-\overline{\frac{1}{3}-\frac{1}{6}}\right)\right\}\right]$

Given expression:

#### Question 1:

8 + 4 ÷ 2 × 5 = ?
(a) 30
(b) 50
(c) 18
(d) none of these

(c ) 18

Explanation:
= 8 + 4 ÷ 2 × 5
= 8 + 2 × 5
= 8 + 10 = 18

#### Question 2:

54 ÷ 3 of 6 + 9 = ?
(a) 117
(b) 12
(c) $\frac{6}{5}$
(d) none of these

( b ) 12

Explanation:
= 54 ÷ 3 of 6 + 9
= 54 ÷ (3  x 6) + 9
= 54 ÷ 18 + 9
= 3 + 9 = 12

#### Question 3:

13 − (12 − 6 ÷ 3) = ?
(a) 11
(b) 3
(c) $\frac{7}{3}$
(d) none of these

(b ) 3

Explanation:
= 13 - (12 - 6 ÷ 3)
= 13 - (12 - 2)
= 13 - 10 = 3

#### Question 4:

1001 ÷ 11 of 13 = ?
(a) 7
(b) 1183
(c) 847
(d) none of these

(a ) 7

Explanation:
= 1001 ÷  11 of 13
= 1001 ÷ ( 11 x 13)
= 1001 ÷ 143 = 7

#### Question 5:

133 + 28 ÷ 7 − 8 × 2 = ?
(a) 7
(b) 121
(c) 30
(d) none of these

(b) 121

Explanation:
Given expression:
= 133 + 28 $÷$ 7 - 8 ⨯ 2
= 133 + 4 - 8 ​⨯2              [Performing division]
= 133 + 4 - 16                 [Performing multiplication]
= 137 - 16                       [Performing addition]
= 121                              [Performing subtraction]

#### Question 6:

3640 − 14 ÷ 7 × 2 = ?
(a) 3636
(b) 1036
(c) 1819
(d) none of these

(a) 3636

Explanation:
Given expression:
= 3640 - 14 $÷$ 7 ⨯ 2
​= 3640 - 2  ​⨯2               [Performing division]
= 3640 - 4                    [Performing multiplication]
= 3636                          [Performing subtraction]

#### Question 7:

100 × 10 − 100 + 2000 ÷ 100 = ?
(a) 29
(b) 920
(c) none of these

(b) 920

Explanation:
Given expression:
= 100 ⨯ 10 $-$ 100 + 2000 $÷$ 100
​= 100 ⨯ 10 $-$ 100 + 20                  [Performing division]
= 1000 $-$ 100 + 20                        [Performing multiplication]
= 1020 $-$100                                 [Performing addition]
= 920                                   ​        [Performing subtraction]

#### Question 8:

(a) 25
(b) 23
(c) none of these

(b) 23
Explanation:

Given expression:
= 27 $-$ [18 $-$ {16 $-$ (5 $-$ $\overline{)4-1}$)}]
=  27 $-$ [18 $-$ {16 $-$ (5 $-$ 3)}]                          (Removing bar)
= 27 $-$ [18 $-$ {16 $-$ 2}]                                   (Removing parentheses)
= 27 $-$ [18 $-$ 14]                                            (Removing braces)
= 27 $-$ 4                                                        (Removing square brackets)
= 23

#### Question 9:

(a) 29
(b) $\frac{520}{17}$
(c) none of these

(a) 29
Explanation:
Given expression:
= 32 $-$ [48 $÷$ {36 $-$ ( 27 $-$ $\overline{)16-9}$)}]
=  32 $-$ [48 $÷$ {36 $-$ ( 27 $-$ 7)}]                    (Removing bar)
= 32 $-$ [48 $÷$ {36 $-$20}]                               (Removing parentheses)
= 32 $-$ [48 $÷$ 16]                                          (Removing braces)
= 32 $-$ 3                                                      (Removing square brackets)
= 29

#### Question 10:

8 − [28 ÷ {34 − (36 − 18 ÷ 9 × 8)}] = ?
(a) 6
(b) $6\frac{4}{9}$
(c) none of these

(a ) 6

Explanation:
Given expression:
= 8 $-$ [28 ÷ {34 $-$ (36 $-$ 18 ÷ 9 × 8)}]                        [Performing division]
= 8 $-$ [28 ÷ {34 $-$ (36 $-$ 2 ×  8)}]                               [Performing multiplication]
= 8 $-$ [28 ÷ {34 $-$ (36 $-$ 16)}]
= 8 $-$ [28 ÷ {34 $-$ 20}]                                              [Removing parentheses]
= 8 $-$ [28 ÷ 14]                                                         [Removing braces]
= 8 $-$ 2 = 6                                                               [Removing square brackets]

#### Question 1:

Simplify:

We have:
16 - [11 + {8 - (6 -$\overline{)4-2}$ )}]
= ​16 - [11 + {8 - (6 - 2)}]         (Removing bar)
= ​16 - [11 + {8 - 4}]
= ​16 - [11 + 4]                           (Removing barces)
= 16 - 15                                          (Removing square brackets)
= 1

#### Question 2:

Simplify:

We have:
16 + 8 $÷$ 4 $-$ 2 $×$ 3
16 + 2 $-$ 2 $×$ 3             (Division)
16 + 2 $-$ 6                   (Multiplication)
= 18 $-$ 6                           (Addition)
= 12

#### Question 3:

Simplify:

Given expression:
36 - [18 - {14 - (15 - 4 ÷ 2 × 2)}]                                     [Performing division]
= 36 - [18 - {14 - (15 - 2 × 2)}]                                           [Performing multiplication]
= 36 - [18 - {14 - (15 - 4)}]
= 36 - [18 - {14 - 11}]                                                        [Removing parentheses]
= 36 - [18 - 3]                                                                    [Removing braces]
= 36 - 15                                                                           [Removing square brackets]
= 21

#### Question 4:

(a) 8
(b) 2
(c) 17
(d) none of these

(c) 17
We have:
15 + 5 ÷ 5 x 2
= 15 +1 x 2              (Performing division)
= 15 + 2                  (Performing multiplication)
= 17

#### Question 5:

(a) 16
(b) 14
(c) $27\frac{5}{7}$
(d) none of these

(c) $27\frac{5}{7}$
We have:
16 - 2 ÷ 7 +  6 × 2
= 16 - $\left(\frac{2}{7}\right)$ + 6 × 2                                                                [Performing division]
= 16 - $\left(\frac{2}{7}\right)$ + 12                                                                    [Performing multiplication]
= 28 - $\left(\frac{2}{7}\right)$                                                                            [Performing addition]
=                                     [Performing subtraction]

#### Question 6:

(a) 117
(b) 12
(c) $\frac{6}{5}$
(d) none of these